2019
DOI: 10.1186/s13643-019-1256-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy across chronic pain disorders: a systematic review protocol synthesising anatomical and metabolite findings in chronic pain patients

Abstract: BackgroundChronic pain is pain greater than 3 months duration that may result from disease, trauma, surgery, or unknown origin. The overlap between the psychological, behavioural, and management aspects of pain suggest that limbic brain neurochemistry plays a role in chronic pain pathology. Proton magnetic resonance spectroscopy (1H-MRS) can evaluate in vivo brain metabolites including creatine, N-acetylaspartate, myo-inositol, choline, glutamate, glutamine, and gamma-aminobutyric acid in chronic pain; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Nevertheless, there is a lack of evidence towards investigating therapeutic effects on the supraspinal structures in low back pain. In this study, based on an a priori hypothesis, we investigated for the first time the supraspinal structures during HF‐10 SCS over time in patients with FBSS in specific RoIs involved in chronic pain conditions 24 . This so‐called RoI VBM analysis is more sensitive than a whole‐brain VBM and specifically useful for the evaluation of an a priori hypothesis 42,43 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there is a lack of evidence towards investigating therapeutic effects on the supraspinal structures in low back pain. In this study, based on an a priori hypothesis, we investigated for the first time the supraspinal structures during HF‐10 SCS over time in patients with FBSS in specific RoIs involved in chronic pain conditions 24 . This so‐called RoI VBM analysis is more sensitive than a whole‐brain VBM and specifically useful for the evaluation of an a priori hypothesis 42,43 …”
Section: Discussionmentioning
confidence: 99%
“…This method enables the identification of volumetric changes in local brain regions. More specifically, the following regions were investigated: bilateral hippocampus, thalamus, dorsolateral prefrontal cortex, ventromedial prefrontal cortex, anterior cingulate, posterior cingulate, insular regions, and parietal lobe 24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Injuries at work may be one of the reasons why workers report the onset of pain or persistent discomfort over long periods of time (≥3 months) [13,14]. This chronic pain (CP) may end up affecting workers' quality of life and work performance [14], above all in the more physically demanding professions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies using a variety of non-invasive neuroimaging techniques in vivo have demonstrated CP-related brain alterations in the neurochemical profile, regional gray matter (GM), regional spontaneous activity, functional connectivity and networks. [ 5 16 ] The key altered brain areas, including the sensorimotor, prefrontal, cingulate, and insular cortices in the sensorimotor network, default mode network, and salience network, were not only involved in sensory processing, but also in cognitive-affective processing, which have helped us to understand the maladaptive neurobiological mechanisms leading to the development of CP. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%